Influencer Credibility as A Source of Travel Information for Generation Z to Bali - Nyoman Nariyani, Ni; Putu Oka Agustini, Ni; Kristiono Liestiandre , Hanugerah (Green Publisher Indonesia, 2024)
The development of technology is increasingly rapid, so tourism business managers must keep up with existing technological developments. Social media, especially Instagram, is one of the most widely used platforms in the world, especially for Generation Z. However, some respondents use Instagram for information and entertainment and there is a problem that the information obtained is sometimes not in accordance with reality, especially tourist information. This shows that there is still a lack of credible influencer filtering used in disseminating information about a product or place. This study aims to examine the differences in the interests of Generation Z in assessing the credibility of influencers as a source of tourism information to Bali. In the study, the researcher used a quantitative approach with data analysis used, namely the Multivariate of Variance Test (MANOVA). The number of samples used was 110 respondents per type of tourist. The sampling technique is non-probability sampling with a purposive sampling approach. The results of the study revealed that both domestic and foreign tourist groups judged influencers by their attractiveness to create a feeling of trust in the content disseminated. Meanwhile, for the gender group, they have the same perspective in assessing the credibility of an influencer.